Infants help singers of familiar songs. (28th February 2018) - Cirelli, Laura K.; Trehub, Sandra E.
Infants are highly selective in their help to unfamiliar individuals. For example, they offer more help to partners who move synchronously with them rather than asynchronously and to partners who interact with them in a "nice" rather than "mean" manner. Infant-directed song and speech may also encourage infant helping by signaling caregiver quality. In the present study, we investigated the effect of infant-directed song and recitation on 14-month-old infants' subsequent helpfulness and proximity-seeking in relation to unfamiliar performers. During a 2.5-minute exposure phase, infants sat on their caregiver's lap opposite an experimenter who sang "The Ants Go Marching" (song condition), recited the lyrics (recitation condition), or remained silent while parents read them a book (baseline condition). After the exposure phase, infants participated in a series of helping tasks that necessitated the return of objects dropped "accidentally". Infants in the song and recitation conditions helped more than those in the baseline condition, but their helping of singers was moderated by song familiarity. Specifically, the extent of help directed to singers correlated positively with song familiarity. Singing (and to some extent, recitation) also encouraged infants to seek proximity with the experimenter. The findings indicate that rhythmic song and recitation by an unfamiliar adult foster infant affiliative behavior, but familiar songs may have special social importance.